2020
DOI: 10.1038/s41598-020-58910-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pulse wave transit time analysis for non-invasive cardiac output quantification in pregnant patients

Abstract: Pregnant patients undergoing minimally-invasive foetoscopic surgery for foetal spina bifida have a need to be subjected to advanced haemodynamic monitoring. this observational study compares cardiac output as measured by transpulmonary thermodilution monitoring with the results of non-invasive estimated continuous cardiac output monitoring. transpulmonary thermodilution-based pulse contour analysis was performed for usual anaesthetic care, while non-invasive estimated continuous cardiac output monitoring data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The study of Schneck et al showed that for SS patients with myocardial injury, PICCO-guided fluid resuscitation can reduce the occurrence of fluid overload, reduce the degree of organ dysfunction, and shorten the duration of mechanical ventilation and ICU stay [ 58 ]. CVP is used as an indicator to evaluate the state of vascular volume because of its simplicity, but some studies have shown that CVP is not significantly correlated with blood volume [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study of Schneck et al showed that for SS patients with myocardial injury, PICCO-guided fluid resuscitation can reduce the occurrence of fluid overload, reduce the degree of organ dysfunction, and shorten the duration of mechanical ventilation and ICU stay [ 58 ]. CVP is used as an indicator to evaluate the state of vascular volume because of its simplicity, but some studies have shown that CVP is not significantly correlated with blood volume [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, PWTT fluctuations can be observed noninvasively using conventional vital sign measurements. PWTT measurement remains a potential simple and affordable alternative to systemic vascular resistance measurements in patients with systemic diseases who receive dental treatment [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pulse wave transit time analysis method and bioimpedance method are also suggested non-invasive CO measurement methods. But pulse wave transit time was reported a poor correlation with CO measured by a standard method in significantly reduced vascular resistance condition 8 . Bioreactance method was also affected by lung injuries and fluid accumulation within the thorax 32 other than actual CO changes.…”
Section: The Potential Advantages Of Our Methodmentioning
confidence: 99%
“…Cardiac MRI 2 Volume clamp method 5 Impedance cardiography 6 Bioreactance method 7 Pulse wave transit time analysis 8 Inert gas rebreathing technique 9 Procedure for LFCT measurement and data exclusion criteria. Patients were asked to lay down, and an air-flow sensor (TR-101A, Nihon Kohden Corp., Tokyo, Japan) was set on the nose.…”
Section: Echocardiogrammentioning
confidence: 99%